2017
DOI: 10.1590/0001-3765201720170056
|View full text |Cite
|
Sign up to set email alerts
|

Cryopreservation of banana’s cv Grand Naine in vitro rhizomes

Abstract: The preservation of banana genetic material is usually performed through seedlings. However, most banana cultivars do not produce seed and are propagated vegetatively. Therefore, cryopreservation is a feasible technique that allows the preservation of banana genotypes indefinitely. For the success of cryopreservation protocols, the selection of cryoprotectants and pre-freezing techniques are important factor. Therefore, the objective of this study was to verify the effects of different cryoprotectants with and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 47 publications
(26 reference statements)
0
1
0
Order By: Relevance
“…Vitrification is a process where cryoprotectant solution solidifies into a metastable amorphous solid known as glass (Roque-Borda et al, 2021). The method uses concentrated cryoprotectants that can penetrate and dehydrates the cell, hence preventing the formation of intra-and extracellular ice crystals in cells and tissues that can cause damage to the cells (Londe et al, 2018). The procedure does not require the use of an expensive programmable freezer (Jiroutová & Sedlák, 2020) making it cheaper than the other methods of cryopreservation of plant materials.…”
Section: Introductionmentioning
confidence: 99%
“…Vitrification is a process where cryoprotectant solution solidifies into a metastable amorphous solid known as glass (Roque-Borda et al, 2021). The method uses concentrated cryoprotectants that can penetrate and dehydrates the cell, hence preventing the formation of intra-and extracellular ice crystals in cells and tissues that can cause damage to the cells (Londe et al, 2018). The procedure does not require the use of an expensive programmable freezer (Jiroutová & Sedlák, 2020) making it cheaper than the other methods of cryopreservation of plant materials.…”
Section: Introductionmentioning
confidence: 99%
“…Phloroglucinol (1,3,5-trihydroxybenzene) is a phenolic compound that has a signi cant importance to plant tissue culture, since it has been considered as an alternative supplement to plant growth regulators (Teixeira da Silva et al 2013; Aremu et al 2015). In cryopreservation, phloroglucinol is utilized as a cryoprotectant because it has a cryoprotective action against oxidative stress and associated metabolism brought on by free radicals, which increases the lifetime of cryopreserved explants (Londe et al 2017). Although the exact mechanism by which phloroglucinol promotes growth is unclear, one study has found that the substance has a signi cant impact on the lignin biosynthetic pathway by enhancing the expression of key enzymes, including cinnamyl alcohol dehydrogenase (CAD), cinnamoyl-CoA reductase (CCR), and Caffeic acid O-methyltransferase, which increases lignin production (Farmer, 1985).…”
Section: Introductionmentioning
confidence: 99%